2016
DOI: 10.18632/oncotarget.10342
|View full text |Cite
|
Sign up to set email alerts
|

β-cell insulin receptor deficiency duringin uterodevelopment induces an islet compensatory overgrowth response

Abstract: The presence of insulin receptor (IR) on β-cells suggests that insulin has an autocrine/paracrine role in the regulation of β-cell function. It has previously been reported that the β-cell specific loss of IR (βIRKO) leads to the development of impaired glycemic regulation and β-cell death in mice. However, temporally controlled βIRKO induced during the distinct transitions of fetal pancreas development has yet to be investigated. We hypothesized that the presence of IR on β-cells during the 2nd transition pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Experimental MIP-CreERT + ; β1itg fl/fl ( MIPβ1KO ) mice are MIP-CreERT positive (268bp) with both β1 integrin alleles floxed by LoxP sites (β 1itg fl/fl , 280bp). MIP-CreERT-; β1itg fl/fl and MIP-CreERT +; β1itg +/+ ( Controls) mice are either MIP-CreERT negative with both β1 integrin alleles floxed or MIP-CreERT positive with wild-type β1 integrin alleles ( β1itg +/+ , 160bp) [ 30 ]. All protocols were approved by the Animal Use Subcommittee at the University of Western Ontario in accordance with the guidelines of the Canadian Council of Animal Care.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental MIP-CreERT + ; β1itg fl/fl ( MIPβ1KO ) mice are MIP-CreERT positive (268bp) with both β1 integrin alleles floxed by LoxP sites (β 1itg fl/fl , 280bp). MIP-CreERT-; β1itg fl/fl and MIP-CreERT +; β1itg +/+ ( Controls) mice are either MIP-CreERT negative with both β1 integrin alleles floxed or MIP-CreERT positive with wild-type β1 integrin alleles ( β1itg +/+ , 160bp) [ 30 ]. All protocols were approved by the Animal Use Subcommittee at the University of Western Ontario in accordance with the guidelines of the Canadian Council of Animal Care.…”
Section: Methodsmentioning
confidence: 99%
“…Pancreatic sections were prepared from the entire length of the pancreas and stained with primary antibodies listed in Supplementary Table 2 . Quantitative evaluations of islet number, size, and alpha-cell and beta-cell mass were performed using Image-Pro software (MediaCybernetics, Rockville, MD, USA) [ 14 , 30 ]. A minimum of 10 islets per pancreas was manually traced from 5 to 6 different mice per experimental group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the impact of loss of IR on β cell replication is still a matter of debate. Although some studies showed no or positive effects of loss of IR on murine β cell expansion [ 54 , 55 ], several other studies showed that IR deficiency reduces mouse β cell proliferation and mass [ [56] , [57] , [58] , [59] ]. Additionally, deletion of insulin inhibitory receptor (inceptor), which desensitizes IR, also enhances β cell division further supporting the direct involvement of IR signaling in β cell propagation [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the tamoxifen-mediated Lats1&2 deletion in adult β-cells, 6-8 weeks old mice were intraperitoneal (i.p) injected with 200 mg/kg tamoxifen (TAM, Sigma-Aldrich, T5648) for 5 consecutive days. For the early β-cell Lats1&2 deletion, female Lats1&2 fl/fl mice and male mice carrying MIP CreER ; Lats1&2 fl/fl were timed mated and after 12 days, the pregnant mice were injected with 100 mg/kg tamoxifen once [18]. PCR was used for validation of knockout alleles (S Table 2).…”
Section: Generation Of Conditional Knockout Micementioning
confidence: 99%